2012
DOI: 10.1097/fbp.0b013e3283576999
|View full text |Cite
|
Sign up to set email alerts
|

Increased feeding and body weight gain in rats after acute and chronic activation of RXFP3 by relaxin-3 and receptor-selective peptides

Abstract: This paper provides a review of the effects of relaxin-3 and structurally related analogues on food intake and related behaviours, in relation to hypothalamic neural networks and chemical messengers known to control feeding, metabolism and body weight, including other neuropeptides and hormones. Soon after relaxin-3 was discovered, pharmacological studies identified the ability of the native peptide to stimulate feeding acutely in adult rats. Although interpretation of these data was confounded by ligand cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 82 publications
(147 reference statements)
1
43
0
Order By: Relevance
“…Relaxin-3 is predominantly expressed in gamma-aminobutyric acid (GABA) neurons in the hindbrain nucleus incertus, which projects widely to forebrain areas, including the amygdala, bed nucleus of the stria terminalis (BNST), hippocampus, and lateral hypothalamus, which also express high levels of RXFP3 (11,15,(17)(18)(19)(20)(21)(22). This pattern of innervation, along with findings that relaxin-3 can modulate (i) food intake (23)(24)(25), (ii) responses to stress (20,26,27), (iii) arousal (28,29), and (iv) interactions with the corticotropin-releasing factor (CRF) systems (20,26), led us to hypothesize that relaxin-3 may modulate aspects of behavior related to substance use and abuse. Such a role would parallel that of other neuropeptides, such as orexin/hypocretin (30,31), galanin (32), and melanin-concentrating hormone (33).…”
Section: Addiction | Dependencementioning
confidence: 99%
“…Relaxin-3 is predominantly expressed in gamma-aminobutyric acid (GABA) neurons in the hindbrain nucleus incertus, which projects widely to forebrain areas, including the amygdala, bed nucleus of the stria terminalis (BNST), hippocampus, and lateral hypothalamus, which also express high levels of RXFP3 (11,15,(17)(18)(19)(20)(21)(22). This pattern of innervation, along with findings that relaxin-3 can modulate (i) food intake (23)(24)(25), (ii) responses to stress (20,26,27), (iii) arousal (28,29), and (iv) interactions with the corticotropin-releasing factor (CRF) systems (20,26), led us to hypothesize that relaxin-3 may modulate aspects of behavior related to substance use and abuse. Such a role would parallel that of other neuropeptides, such as orexin/hypocretin (30,31), galanin (32), and melanin-concentrating hormone (33).…”
Section: Addiction | Dependencementioning
confidence: 99%
“…The neuroanatomy of the relaxin-3/RXFP3 system suggests a broad role as an ascending neuromodulatory network [20,21], akin to the monoamine systems including serotonin, and noradrenaline [22][23][24][25]. Anatomical and functional data [15][16][17][18] suggest that relaxin-3/RXFP3 systems may interact directly with monoamine [19,26] and other peptide systems [27][28][29], and/or act at shared downstream limbic and hypothalamic target areas to modulate 'anxiety' and other stress-related responses [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased feeding and modest body weight gain following acute and chronic central RXFP3 activation is well characterised in the rat (see [31] for review), but icv or intrahypothalamic injection of a specific RXFP3 agonist does not induce food intake in mice [44] and studies of relaxin-3 and RXFP3 knockout (KO) mice reveal no differences in body weight relative to their wildtype (WT) littermates [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work suggested that the relaxin-3/RXFP3 system may play a role in appetite control, stimulation of the reproductive axis, spatial working memory and arousal (McGowan et al 2005, 2006a,b, 2008, Ma et al 2009, Ganella et al 2012, 2013a. More recent work has suggested a role for relaxin-3 in the modulation of anxiety and depression and alcohol-seeking behaviour (Ryan et al 2013a,b), and there is emerging evidence to suggest that relaxin-3 may regulate the neuro-endocrine stress axis (Ganella et al 2013b).…”
mentioning
confidence: 99%